2018
DOI: 10.14740/cr770w
|View full text |Cite
|
Sign up to set email alerts
|

Deflated Balloon-Facilitated Direct Stenting in Primary Angioplasty (The DBDS Technique): A Pilot Study

Abstract: BackgroundSeveral studies and meta-analyses have shown that direct stenting (DS) may improve clinical outcomes in patients with acute ST-elevation myocardial infarction (STEMI). But in most cases, the thrombolysis in myocardial infarction (TIMI) flow remains ≤ 1 after wire placement. We used deflated balloon to facilitate DS in patients with totally occluded culprit arteries. The aim of this study was to evaluate the feasibility, safety and outcomes of this novel technique in patients with STEMI in real-world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…More recently, the 5-year follow-up of EXAMINATION trial demonstrated a reduction in the patient-oriented endpoints, device-oriented endpoints, stent thrombosis and all-cause mortality with DES [37]. Stenting with new-generation DES is thus recommended over BMS for primary PCI [2]. The results of the present study confirm these findings with a favourable 1-year safety and efficacy profile.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…More recently, the 5-year follow-up of EXAMINATION trial demonstrated a reduction in the patient-oriented endpoints, device-oriented endpoints, stent thrombosis and all-cause mortality with DES [37]. Stenting with new-generation DES is thus recommended over BMS for primary PCI [2]. The results of the present study confirm these findings with a favourable 1-year safety and efficacy profile.…”
Section: Discussionsupporting
confidence: 80%
“…Major and minor bleeding was defined using the Thrombolysis in Myocardial Infarction (TIMI) bleeding criteria [22]. Obesity was defined as body mass index > 25 kg/m2 [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe coronary artery disease and a low LVEF, the evaluation of viability in regions with chronic contractile dysfunction has been shown to predict improvement of function after revascularization [2], [3], [4], [5], [6], [7], [8], [24], [25]. The current study was done to compare the most widely available and commonly used modalities, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports show that > 50% of such patients may have viable myocardium [1]. Revascularization improves left ventricular ejection fraction (LVEF), heart failure symptoms and prognosis predominantly in patients with viable myocardium [2], [3], [4], [5], [6], [7], [8]. Though some recent studies provided contrary results, they had several significant limitations and confounding factors [9], [10].…”
Section: Introductionmentioning
confidence: 99%